Depiction of a Dikapala on the western wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
On the western wall of the garbhagriha (sanctum sanctorum) of Shiva Temple 1, a dikapala (deities of the cardinal directions) is illustrated on the corner projection. This two-armed deity is portrayed with a khadga (sword) in his right hand while his left-hand rests on his thigh. Adorned with a crown and jewellery, the deity is accompanied by his vahana (mount), which is depicted at the base.